Academician Albinas Rimka (1886–1944) and science of statistics in Lithuania: application of mathematics - Banionis, Juozas (Lietuvos matematikos rinkinys, 2017)
The scientist, statesman, academician Albinas Rimka (1886–1944) is famous in Lithuanian historiography as a creator of independent Lithuania. First of all, his merits as a politician and economist are to be mentioned. Albinas Rimka is considered to be the founding father of science of statistics in Lithuania in 1920–1940. In the textbooks on fundamentals of statistics and at lectures which Albinas Rimka delivered at university, the academician based statistical methods upon the main verities of high mathematics including elements of mathematical analysis, theory of probability, and mathematical statistics. In his textbooks, we can find elements of application of mathematics which were not given attention by other researchers (historians and economists) in Lithuania. The article tries to fill in the gap in research of origins of science of statistics in Lithuania with the help of the analysis of Albinas Rimka’s textbooks.
Keywords: mathematical statistic; probability theory; mathematical analysis